A prevalence survey of every-day activities in pregnancy - Hadfield Ruth M; Ford Jane B; Lain Samantha J; Roberts Christine L (BMC, 2010)
Abstract Background Research into the effects of common activities during pregnancy is sparse and often contradictory. To examine whether common activities are an acute trigger of pregnancy complications the prevalence of these activities are necessary to determine sample size estimates. The aim of this study is to ascertain the prevalence of selected activities in any seven day period during pregnancy. Methods The study was conducted in the antenatal clinic of a teaching hospital with tertiary obstetric and neonatal care in Sydney, Australia between August 2008 and April 2009. Women who were at least 20 weeks pregnant and able to read English completed a questionnaire to assess whether they had performed a list of activities in the seven days prior to survey completion. Results were analysed using frequency tabulations, contingency table analyses and chi square tests. Results A total of 766 surveys were completed, 29 surveys were excluded as the women completing them were less than 20 weeks pregnant, while 161 women completed the survey more than once. Ninety seven per cent of women completed the survey when approached for the first time, while 87% completed the survey when approached a subsequent time. In the week prior to completing the survey 82.6% of women had consumed a caffeinated beverage, 42.1% had had sexual intercourse, 32.7% had lifted something over 12 kilograms, 21.4% had consumed alcohol and 6.4% had performed vigorous exercise. The weekly prevalence of heavy lifting was higher for multiparous women compared to nulliparous women. Conclusions The results of this study can be used to inform future research into activities as acute triggers of pregnancy complications.